DEVELOPMENT STAGES AND SPATIAL FORMATION OF RECREATIONAL AND HEALTH-REHABILITATION COMPLEXES - Kurbanova Dilnoza (TADQIQOTLAR, 2026)
Abstract This  study  examines  the  development  stages  and  spatial  formation  of recreational and health-rehabilitation complexes, particularly in desert and semi-desert regions. The research highlights the transformation of such complexes from simple therapeutic  environments  into  multifunctional  spatial  systems  influenced  by environmental,  social,  and  technological  factors.  The  findings  demonstrate  that climate-responsive  planning,  compact  spatial  organization,  and  bioclimatic  design significantly improve environmental performance and user comfort